Movimentos feministas insurgentes: microativismos, performances urbanas, vulnerabilidades em resistência - Pinto, Amanda Marques (2022)
The theme of this thesis is the mode of resistance and action of collectives of women artists in conditions of vulnerability, that have been organizing themselves throughout different territories (subjective and geographic). Among them, we highlight: Guerrilla Girls (United States), Polvo de Gallina Negra (Mexico), Mujeres Creando (Bolivia), Las Tesis (Chile), Pussy Riot (Russia), Frente Transfeminista de Resistência Marikon (Colombia), Women in Black (Israel), Tomorrow Girls Troop (Japan), Mulheres de Buço (Brazil) e Sensel/EX (Brazil). With the theoretical foundation, we include a historical context organized by Margareth Rago (2016;2017) and Sonia Alvarez (2003) who cartographs the history of women, inside and outside the artistic context. In addition, we convened Judith Butler's discussions (1997; 2006; 2016; 2017; 2018) on performativity, collective and interpelation, focusing on her partnership with Zeynep Gambetti (2016) to discuss how states of vulnerability can trigger collective resistance actions within a micropolitical logic. We also present some hypotheses of Michel Foucault (2008; 2014) related to the problematizations of neoliberal practices and the notion of government of themselves. The corpusmedia theory of Christine Greiner and Helena Katz (2005; 2015) based the analysis of the political-cognitive relations of the bodies with the various environments. As a result of the research, we observed that women are increasingly excluded from macropolitics, but act incessantly with their insurgent microactivism, using art as a way to produce new knowledge and manifestos through life